ERROR ANALYSIS ON INFORMATION AND TECHNOLOGY STUDENTS’ SENTENCE WRITING ASSIGNMENTS - Rentauli Mariah Silalahi (IJEE (Indonesian Journal of English Education), 2014)
Students’ error analysis is very important for helping EFL teachers to develop their teaching materials, assessments and methods. However, it takes much time and effort from the teachers to do such an error analysis towards their students’ language. This study seeks to identify the common errors made by 1 class of 28 freshmen students studying English in their first semester in an IT university. The data is collected from their writing assignments for eight consecutive weeks. The errors found were classified into 24 types and the top ten most common errors committed by the students were article, preposition, spelling, word choice, subject-verb agreement, auxiliary verb, plural form, verb form, capital letter, and meaningless sentences. The findings about the students’ frequency of committing errors were, then, contrasted to their midterm test result and in order to find out the reasons behind the error recurrence; the students were given some questions to answer in a questionnaire format. Most of the students admitted that careless was the major reason for their errors and lack understanding came next. This study suggests EFL teachers to devote their time to continuously check the students’ language by giving corrections so that the students can learn from their errors and stop committing the same errors.